Analisis pengaruh ekspor, produk domestik bruto dan neraca transaksi berjalan terhadap cadangan devisa di ASEAN-5 - Tri Artha Aritonang, Novita; Hodijah, Siti; Nurjanah, Rahma (Jurnal Paradigma Ekonomika, 2024)
This research aims to analyze and find out: 1). development of foreign exchange reserves, exports, gross domestic product and current account balance in ASEAN-5 for the 1991-2020 period. 2). The influence of exports, GDP and current account balance (NTB) on foreign exchange reserves in ASEAN-5 in 1991-2020. The data used in this research is secondary data sourced from the world bank. The method used is a descriptive and quantitative method using panel data regression statistical analysis tools. The results of this research show that 1). During the 1991-2020 period, the development of foreign exchange reserves, exports, gross domestic product (GDP) and current account balance (NTB) in ASEAN-5 soared with an increasing average. 2). simultaneously and partially the export variable, gross domestic product has a positive and significant effect on foreign exchange reserves in ASEAN-5.